Clonality analysis in primary oral squamous cell carcinoma and related lymph-node metastasis revealed by TP53 and mitochondrial DNA next generation sequencing analysis. Issue 2 (March 2015) - Morandi, Luca; Tarsitano, Achille; Gissi, Davide; Leonardi, Elisa; Balbi, Tiziana; Marchetti, Claudio; Montebugnoli, Lucio; Foschini, Maria Pia
Abstract The chance of developing a neck nodal metastasis after initial treatment of oral squamous cell carcinoma varies from 12.4% to 62%. Despite being the main reason for cancer-related mortality, nodal metastases are still rarely subjected to molecular analyses, and our knowledge of the clonal heterogeneity of multiple lesions within the same patient is limited. The aim of the present study was to evaluate the relationship between primary oral cancer and lymph node metastasis in a series of patients with synchronous and metachronous metastases by 2 clonality tests: mt-DNA and TP53 sequence analysis. The study population consisted of 10 consecutive patients. Data identified in this study demonstrate that our assay based on next-generation analysis of TP53 and mt-DNA is simple, is reliable, allows high throughput, and may be applied to retrospective cases. The combination of mt-DNA and TP53 data analysis helped us to evaluate more precisely and consistently the genetic relationship among different tumor clones.